2016
DOI: 10.1007/s40264-016-0464-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk–Benefit Profile of Direct-Acting Oral Anticoagulants in Established Therapeutic Indications: An Overview of Systematic Reviews and Observational Studies

Abstract: Since 2008, the direct-acting oral anticoagulants (DOACs) have expanded the therapeutic options of cardiovascular diseases with recognized clinical and epidemiological impact, such as non-valvular atrial fibrillation (NVAF) and venous thromboembolism (VTE), and also in the preventive setting of orthopedic surgical patients. The large body of evidence, not only from pivotal clinical trials but also from ‘real-world’ postmarketing observational findings (e.g. analytical epidemiological studies and registry data)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 110 publications
2
14
0
Order By: Relevance
“…Meta-analyzes with up to 50,578 patients using NOACs showed reduction of stroke, intracranial hemorrhage and mortality, but there was a higher gastrointestinal bleeding rate compared to the group using warfarin (Miller et al, 2012;Capodanno et al, 2013;Ruff et al, 2014). Recent systematic review, including meta-analyzes and observational studies, with overlapping studies, comparing patients on NOACs and those using warfarin, for the consolidated indications (non-valvular AF and deep venous thrombosis/pulmonary thromboembolism), showed results similar to those described above (Raschi et al, 2016). Post-marketing studies are non-randomized, retrospective studies, but reflect the real-world clinical practice.…”
Section: Effectiveness and Safety Of Noacssupporting
confidence: 59%
“…Meta-analyzes with up to 50,578 patients using NOACs showed reduction of stroke, intracranial hemorrhage and mortality, but there was a higher gastrointestinal bleeding rate compared to the group using warfarin (Miller et al, 2012;Capodanno et al, 2013;Ruff et al, 2014). Recent systematic review, including meta-analyzes and observational studies, with overlapping studies, comparing patients on NOACs and those using warfarin, for the consolidated indications (non-valvular AF and deep venous thrombosis/pulmonary thromboembolism), showed results similar to those described above (Raschi et al, 2016). Post-marketing studies are non-randomized, retrospective studies, but reflect the real-world clinical practice.…”
Section: Effectiveness and Safety Of Noacssupporting
confidence: 59%
“…The relative safety of DOACs versus warfarin in non-valvular AF patients [ 9 11 ], or versus heparin in the treatment and prevention of recurrence of venous thromboembolism [ 12 14 ], has been demonstrated in large-scale randomized clinical trials (RCTs), and has been confirmed globally by observational studies [ 15 , 16 ]; however, both clinical trials and observational studies have mainly focussed on bleeding adverse events to date [ 17 ]. Postmarketing data, including pharmacovigilance reports [ 18 ] and case reports, have raised concerns about other, albeit rarer, non-bleeding adverse events that could not be detected by RCTs due to intrinsic limitations, such as small sample size and short follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…VKAs have also been the cornerstone for long-term prevention of recurrent VTE (Kearon et al, 2012). However, recent evidence suggests that non-vitamin K oral anticoagulants (NOACs), including apixaban, dabigatran, edoxaban, and rivaroxaban, may offer an improved benefitrisk profile than VKAs for patients with VTE (Raschi, Bianchin, Ageno, De Ponti, & De Ponti, 2016). A new entrant to the NOAC therapeutics class is betrixaban, which was recently approved for VTE prophylaxis in adult patients with acute illness.…”
Section: Introductionmentioning
confidence: 99%